Experimental Study of MgCl2 ⋅ 6 H2O as Thermochemical Energy Storage Material. Issue 10 (4th September 2018) - Kohler, Tobias; Biedermann, Thomas; Müller, Karsten
Abstract: Hydrates of magnesium chloride are interesting as a thermochemical energy storage material. An open storage system was set‐up, which enables the reaction of water vapor with the salt hydrate at a given relative humidity. It is demonstrated that hydrates of magnesium chloride are only suited if the relative humidity is below 30 %. Otherwise the hygroscopic salt will cause the formation of an aqueous, liquid phase. This liquid inhibits mass transport and leads to the agglomeration of particles. As a consequence of the low partial pressure of the water, the reaction is very slow. Therefore, rather low effective energy densities of around 300 kJ kg −1 were measured. A way to enable higher humidities is to use a solid support like zeolite 13X. However, the adsorption of water vapor on the zeolite, without magnesium chloride, reached higher energy densities even at low relative humidity. Thus, it must be concluded that hydration of magnesium chloride for thermochemical energy storage cannot be recommended for most technical applications. Abstract : The potential of magnesium chloride‐hexahydrate as a thermochemical energy storage material was examined under practical aspects. The influence of plant parameters like volume flow and relative humidity of the carrier gas on the maximum reachable temperature as well as on the energy storage density has been evaluated. The low deliquescence relative humidity of the material limits its practical usage as a thermochemical energy storage.